جماليات الحلي واللباس في الشعر الشعبي السوفي دراسة فنية - حمزة, سهيلة; قاسمي, خولة (جامعة الوادي - University of Eloued, 2023)
يتمحور موضوع بحثنا هذا عن إبراز جماليات الحلي واللباس التقليدي في الشعر الشعبي السوفي والتي تحمل في طياته الكثير من الدلالات والرموز التي تكشف لنا عن تراث عريق يحتفظ به المجتمع السوفي. وهي دراسة انثروبولوجية سوسيولوجية فنية وقد استهل البحث بفصل تمهيدي يعرف بمنطقة الدراسة، إذ تعرفنا على طبيعة المنطقة الصحراوية واختلاف أجناسها التي تشكل بذلك نواة ثقافتها. قدمنا في الفصل الأول التأصيل المفاهيمي للمصطلحات، حيث تناولنا فيه مفهوم الجمالية ومفهوم الحلي التقليدية وتاريخ ظهورها وأنواعها ومفهوم اللباس التقليدي وأنواعه ومفهوم الشعر الشعبي، وتسمياتها ونشأته وخصائصه. تطرقنا في الفصل الثاني لدراسة موضوعاتية فنية لنماذج متنوعة من أشعار وادي سوف وإبراز جماليات الحلي واللباس التقليدي من خلال هاته الأشعار التي تعبر عن مدى عراقة وأصالة الحلي واللباس التقليدي للمنطقة، كما أن لكل قصيدة مناسبة ذكرت من أجلها. وقد استعنا في هذا البحث بالجمع الميداني لنصوص الشعرية من طرف الرواة القاطنين في منطقة الدراسة وختمنا البحث بنتائج توصلنا إليها بعد دراسة حاولنا فيها الإلمام بجوانب الموضوع ومع كل هذا لا يزال البحث في حاجة لدراسة وتعمق أكثر. The subject of our research revolves around highlighting the aesthetics of ornaments and traditional dress in the Soviet folk poetry, which carries with it many indications and symbols that reveal to us the ancient heritage preserved by the Soviet society. It is a descriptive, analytical and field study. The research began with an introductory chapter known as the study area, as we got acquainted with the nature of the desert region and its different races, which thus form the nucleus of its culture. In the first chapter, we presented the conceptual rooting of terminology, in which we dealt with the concept of aesthetics, the concept of traditional ornaments, the history of their emergence and their types, the concept of traditional dress and its types, and the concept of popular poetry, its designations, origins and characteristics. In the second chapter, we discussed an objective and artistic study of various models of Wadi Souf poems and highlighting the aesthetics of ornaments and traditional dress through these poems that express the extent of the nobility and originality of the ornaments and traditional dress of the region, and each poem has an occasion for which it is mentioned. In this research, we used the field collection of poetic texts by the narrators living in the study area, and we concluded the research with the results we reached after a study in which we tried to get acquainted with the aspects of the subject, and with all this, the research still needs to be studied and more in-depth.colonialism.
أدب شعبي
Keywords: جماليات- الحلي – اللباس- الشعر الشعبي السوفي; Aesthetics - ornaments - dress - Soviet folk poetr